“An Act for Preventing, Suppressing, and Punishing the Conspiracy and Insurrection of Negroes, and other Slaves,” Acts of Assembly, Passed in the Province of New York, From 1691, to 1718, at 144 (London, 1719) - (:unkn) unknown (General Publisher, 1712)
Prohibition on “any Negro, Indian, Mulatto Slave” from having or using any gun or pistol outside of their master’s presence.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES